Performance, Protest, and Feminism in Latin America - Snyder, Cara K.; González, Sabrina (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2023)
How do activists in Latin America fight for change both online and in the streets? This piece narrates a course on Feminist Protest and Performance in Latin America that explores the limits and possibilities of feminist activism in physical and digital spaces. At this critical historical juncture, feminists across the hemisphere are organizing en masse to demand change and justice, to denounce pervasive misogyny and gender violence, and to envision and realize another world. Drawing on a long history of struggle, they are engaging in performance artivism across multiple platforms including Las Tesis piece El Violador Eres Tu (The rapist is you), under the hashtags #NiUnaMenos (#NotOneWomanLess) and #AbortoLegalYa (#LegalizeAbortionNow), and in massive physical occupations and protests like #OcupaEscola (#OccupyTheSchools). They are mobilizing to condemn femicide, to advocate access to legal abortions in public hospitals, and to introduce comprehensive sex education in public schools. Drawing on these interconnected forms of performance and protest, what Marcela Fuentes refers to as “performance constellations,” women and disidencias sexuales are fighting together for the right to live without fear, to make decisions about their own bodies, and to exist in a more just world. This class asks students to learn from Latin American feminst movements and to connect their insights to our intimate and collective experiences. Beyond the syllabus, this piece offers reflections on the philosophy of co-teaching, transnational activism across the Americas, and modes of embodiment that can happen online. We invite students and educators alike to consider what it might mean to “perform well” in a university class focused on pleasure and solidarity.